2017
DOI: 10.20961/jiep.v16i1.2320
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pembangunan Sektor Pertanian Terhadap Distribusi Pendapatan Dan Kesempatan Kerja Di Indonesia

Abstract: The purpose of this study was to determine the influence of GDP

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
0
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
2
0
0
4
Order By: Relevance
“…This research is in alignment with the findings of Akbar et al ( 2021), which demonstrate that the agricultural sector exerts a deleterious and statistically significant impact on income inequality in Indonesia. Furthermore, it is consistent with the conclusions of Yasrizal & Hasan (2017), who found that agricultural sector income has a detrimental and statistically significant effect on income inequality in Indonesia. Raeskyesa (2020) also identified a significant and negative correlation between the agricultural sector and income inequality in his research.…”
Section: The Effect Of Agricultural Grdp On Income Distribution Inequ...supporting
confidence: 91%
“…This research is in alignment with the findings of Akbar et al ( 2021), which demonstrate that the agricultural sector exerts a deleterious and statistically significant impact on income inequality in Indonesia. Furthermore, it is consistent with the conclusions of Yasrizal & Hasan (2017), who found that agricultural sector income has a detrimental and statistically significant effect on income inequality in Indonesia. Raeskyesa (2020) also identified a significant and negative correlation between the agricultural sector and income inequality in his research.…”
Section: The Effect Of Agricultural Grdp On Income Distribution Inequ...supporting
confidence: 91%
“…Menurut david ricardo menyatakan dalam melakukan proses produksi kemudian menambah salah satu input terus menerus dalam jumlah yang sama sedangkan input yang lain tetap, maka pada awalnya output yang dihasilkan akan mengalami peningkatan. Tetapi kemudian, pada titik tertentu output tersebut akan semakin berkurang (Yasrizal & Hasan, 2017).Sehingga apabila pertambahan jumlah penyerapan tenaga kerja terus terjadi tanpa diikuti dengan faktor produksi lain maka akan mengakibatkan nilai PDRB sektor pertanian akan turun dan begitupun sebaliknya. Penelitian ini juga sejalan dengan (Agustin, 2022) dan (Putri & Soelistyo, 2018) bahwasannya PDRB berpengaruh negatif terhadap penyerapan tenaga kerja.…”
Section: Pembahasanunclassified
“…Hasil penelitian ini sejalan dengan penelitian Yasrizal & Hasan, (2016), yang menyatakan bahwa PDB sektor pertanian memiliki pengaruh yang signifikan dan positif terhadap distribusi pendapatan. Namun, penelitian ini tidak sejalan dengan penelitian Firmansyah et al, (2022), hasil penelitiannya adalah PDRB sektor pertanian tidak signifikan yang memiliki pengaruh negatif terhadap ketimpangan distribusi pendapatan.…”
Section: Pembahasan Pengaruh Pembangunan Sektor Pertanian Terhadap Ke...unclassified